Matching the Catalyst Co(Ii)/(I) Formal Potential of a Macrocyclic Complex to the Reversible Potential of Hydrazine Oxidation for the Highest Activity - Zagal-Moya, J; Zagal-Moya, J; Recio-Cortes, F; Recio-Cortes, F (2013)
In this work we have re-interpreted volcano correlations for the oxidation of hydrazine catalyzed by CoMN4 catalysts and found that the highest catalytic activity is observed when the formal potential of the catalyst matches the reversible potential of the reaction, i.e. the hydrazine/dinitrogen reversible potential, that is 0.4959 V vs. SCE at pH 13. This clearly shows that the formal potential of the catalysts needs to be "tuned" or to be very close to the reversible potential of the target molecule to undergo an ET process. This is also true for other reactions we are studying.© 2013 The Electrochemical Society.